2006
DOI: 10.1016/j.fertnstert.2005.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Fathers over 40 and increased failure to conceive: the lessons of in vitro fertilization in France

Abstract: As an increasing number of couples choose to postpone childbearing, they should be informed that paternal age over 40 years is an important risk factor for failure to conceive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
3
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(87 citation statements)
references
References 33 publications
(17 reference statements)
2
76
3
5
Order By: Relevance
“…Fertility (measured by the probability of clinical pregnancy after intercourse on a given day relative to ovulation) decreased with paternal age, but only among couples composed of a woman aged 35 to 39 years. de La Rochebrochard et al [42] in a retrospective, populationbased sample, including fifty nine French IVF centres reported that men older than 39 years presented more difficulties in having a baby than younger men, when their female couple ages were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Fertility (measured by the probability of clinical pregnancy after intercourse on a given day relative to ovulation) decreased with paternal age, but only among couples composed of a woman aged 35 to 39 years. de La Rochebrochard et al [42] in a retrospective, populationbased sample, including fifty nine French IVF centres reported that men older than 39 years presented more difficulties in having a baby than younger men, when their female couple ages were increased.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by de La Rochebrochard et al (11), the risk of failure to conceive-defined as an absence of intrauterine pregnancy confirmed by echography and an HCG level >1,000 IU-increased markedly with paternal age. The OR for paternal age >40 years compared with <30 years was 1.70 (95% CI, 1.14-2.52).…”
Section: Effect Of Paternal Age On Pregnancy Ratementioning
confidence: 94%
“…Advanced age seems to influence the male reproductive function to a lesser degree than the female's, as evidenced by the fact that babies have been fathered by men aged 70-80 years. Still, sperm from men older than 40 years have been shown to decrease the chance of conception within 12 months (11). In addition, serum steroid levels decrease with advancing age, reflecting altered hypothalamic-pituitary axis regulation and decreased testicular function (12).…”
mentioning
confidence: 99%
“…Some of these studies were prepared on statistically small groups with young volunteers and sperm donors making it difficult to identify an age effect. For this reason data was recently collected on approximately 2,000 men whose partners were totally sterile [7].…”
Section: Introductionmentioning
confidence: 99%